Polityka spójności w świetle strategii lizbońskiej. Między solidarnością regionalną a konkurencyjnością globalną - Urban, Dariusz (Cohesion Politics in the Aspect of Lisbon Strategy. Between Regional Solidarity and Global Competition, 2006)
The aim of the study was to show some questions of EU cohesion in the context of Lisbon Strategy. That work presents the evolution of the meaning of cohesion in the integration process and presents social and economic diversity in EU. The author suggests that problems of cohesion should be estimated in the context of changes happening in global economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 118-126